Meta Synthesis: Analysis of Mathematical Anxiety On Student’s Mathematical Communication Skills - Jahfaludin, Abi; Mariani, Scolastika; Rosyida, Isnaini; Junaedi, Iwan; Cahyono, Adi Nur (JRPM (Jurnal Review Pembelajaran Matematika), 2024)
The purpose of this research is to describe the effect of mathematics anxiety on students' mathematical communication skills. The research method used in this study is meta-synthesis, which is a qualitative systematic review that analyzes articles relevant to the research title. The steps taken are to formulate the research problem, followed by searching for research that has been done that is relevant to the same title, then analyzing the research results in depth. The data collection technique used is non-test by reviewing research that has similar problems to obtain results and conclusions. This study surveyed several national articles. Analysis of the articles resulted in the conclusion that mathematical anxiety has a negative impact on students' mathematical communication skills. Students who have high mathematical anxiety have low mathematical communication skills. While students with low mathematical anxiety have a high level of mathematical communication skills.